Fuzzy expert system on diagnosis atherosclerosis - Mahadi, Lina Farhana (2017)
Heart disease is one of the major factors of death in world wide. Atherosclerosis is the major factor of heart disease. Atherosclerosis is a disease in which plaque builds up inside the arteries that eventually likely to be hardened over time thus narrows the arteries. This project is developed to monitor the atherosclerosis risk among people, which can tell their current health condition. This system could change the perspective of one's life for better living. 20 people consist of 10 male, IO female have been used as a test subject in this project. An Arduino prototype of Atherosclerosis monitors have been developed by applying the fuzzy logic method for testing and analyze the possibilities of atherosclerosis based on several input data obtained from the subject. The selected input data are age, body mass index (BMI), intima media thickness (IMT), blood pressure (BP) and blood glucose level (BGL). Since all the subjects are young in age, the chance of them to have the atherosclerosis is low.